1990
DOI: 10.1128/aem.56.6.1844-1850.1990
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the endo-1,4-beta-glucanase components of Ruminococcus flavefaciens FD-1

Abstract: The extracellular endo-1,4-f0-glucanase components of Ruminococcus flavefaciens FD-1 were analyzed by high-performance liquid chromatography (HPLC) by using DEAE ion-exchange, hydroxylapatite, and gel filtration chromatography and polyacrylamide gel electrophoresis (PAGE). Two endo-1,4-0-glucanase peaks were resolved by DEAE-HPLC and termed endoglucanases A and B. Carboxymethyl cellulose (CMC) zymograms were achieved by enzyme separation using nondenaturing PAGE followed by incubation of the gel on top of a CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 39 publications
0
27
1
Order By: Relevance
“…Recently Cavedon et al [6] have shown that a free-living, mesophilic Clostridiurn (strain C7), secretes an extracellular 700 000-M r multiprotein cellulolytic complex into the culture supernatant. R. flaeefaciens FD-1 secretes two multiprotein complexes in which all the endoglucanases had xylanase activity [5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Cavedon et al [6] have shown that a free-living, mesophilic Clostridiurn (strain C7), secretes an extracellular 700 000-M r multiprotein cellulolytic complex into the culture supernatant. R. flaeefaciens FD-1 secretes two multiprotein complexes in which all the endoglucanases had xylanase activity [5].…”
Section: Resultsmentioning
confidence: 99%
“…Other bacteria appear to secrete their cellulases into the culture fluid. Two enzyme complexes containing 18 endoglucanases have been found in the culture fluid of the rumen anaerobe, R. flavefaciens FD-1 [5], while Clostridium strain C7 and Cellulomonas fimi produce extracellular cellulase complexes [6,7]. Naturally occurring cellulose is usually associated with hemicellulose.…”
Section: Introductionmentioning
confidence: 99%
“…If CMCase negative mutants grew as rapidly on cellulose as wild-type strains and were unable to grow rapidly on L-glu-cans, the claim that non-cellulose-binding CMCases are involved in true cellulose digestion would be dif-¢cult to justify. However, F. succinogenes S85 [32] and cellulolytic ruminococci [2,4,9,10,17] produce a variety of di¡erent CMCases, and this characteristic would confound straightforward mutant selection schemes.…”
Section: Diet Cmcase+ Cmcase3mentioning
confidence: 99%
“…Ruminococcus flavefaciens is a ruminant bacterium highly active on plant cell walls. Two of its strains, R. flavefaciens 17 and R. flavefaciens FD-1, have been extensively studied (Doerner et al, 1990;Doerner et al, 1992;Flint et al, 1993;Vercoe et al, 1995). Both R.…”
Section: Introductionmentioning
confidence: 99%
“…The GH44 EG in this paper, CelB from R. flavefaciens FD-1, has been partially studied (Doerner et al, 1990); it is active on CMC (10 U/mg), oat spelt xylan (3.5 U/mg), and [ 14 C] cellulose (0.0036 U/mg). Temperature and pH optima for CelB have not been published.…”
Section: Introductionmentioning
confidence: 99%